2020
DOI: 10.1590/0104-9224/si25.01
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Interlayer Idle Time as a Temperature Control Technique in Additive Manufacturing of Thick Walls by Means of CMT and CMT Pulse Welding Processes

Abstract: Inserted in the scenario of innovations and technological trends of Industry 4.0, this work aims to obtain detailed knowledge on the influence of idle time between layers as thermal control technique for the Wire Arc Additive Manufacturing (WAAM) with two GMAW process variants of high controllability (CMT and CMT Pulse). The problem focuses on the deposition of thick walls, seeking to emulate the challenges of manufacturing big parts with medium geometric complexity, such as propellers and screws, which usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Para modelos térmicos, os ciclos térmicos da peça durante a fabricação podem ser registrados experimentalmente com instrumentos como termopares, pirômetros e câmeras termográficas (Schoinochoritis et al, 2017). Enquanto o termopar mede a temperatura apenas no ponto onde está instalado, câmeras termográficas (Silva et al, 2020) podem fornecer uma imagem de distribuição de temperatura, provendo informações em uma área maior. No entanto, estas exigem maiores cuidados de calibração.…”
Section: Validações Experimentaisunclassified
“…Para modelos térmicos, os ciclos térmicos da peça durante a fabricação podem ser registrados experimentalmente com instrumentos como termopares, pirômetros e câmeras termográficas (Schoinochoritis et al, 2017). Enquanto o termopar mede a temperatura apenas no ponto onde está instalado, câmeras termográficas (Silva et al, 2020) podem fornecer uma imagem de distribuição de temperatura, provendo informações em uma área maior. No entanto, estas exigem maiores cuidados de calibração.…”
Section: Validações Experimentaisunclassified
“…Thus, long dwell times in-between layers have to be programmed to allow mitigation of heat accumulation and its deleterious consequences. Based on this WAAM problematic, Da Silva et al (2020) developed a thermal management technique named near immersion active cooling (NIAC) for parts built via this manufacturing route and showed an improvement in the heat extracted from them. In such a technique, the preform is continuously kept partially immersed in a liquid (usually water) during the entire deposition time.…”
Section: Introductionmentioning
confidence: 99%
“…They implemented a dwell time between the beads to control the temperature in each of the beads. Silva et al [23] showed that the physical properties of the specimen are affected by the heat accumulation during the WAAM process due to different temperatures in each layer. They found that regulating the operating temperature by introducing idle time helps to minimize heat accumulation.…”
Section: Introductionmentioning
confidence: 99%